Mothers' perception of the care of newborn in the home environment - Gina de Souza Castro Hammel; Laura Tais Loureiro Simas; Luiz Fernando Rodrigues Junior; Claudia Zamberlan; Lurdes Lomba; Dirce Stein Backes (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify mothers' perceptions about caring for newborns in the home environment, from the perspective of complexity thinking. Methods: qualitative, exploratory and descriptive research, carried out between November/2022 and February/2023. Data were collected through individual interviews with 21 mothers from southern Brazil who cared for newborns at home and analyzed using the thematic analysis technique. Results: the four thematic axes resulting from the data analysis: Living amidst order and disorder; embracing singularities; dealing with the certain and the uncertain; support network in the (re)organizing process demonstrate that the mother caring for a newborn in their home environment experiences a distinct and plural adaptive process, which must be welcomed and understood by health professionals who work within the family environment. Final Considerations: the care of newborns in a home environment, in the perception of mothers, requires differentiated attention and a formal or informal support network that considers the unique specificities of each woman/mother in the personal, family and social spheres. Therefore, in addition to the social support network, it is important to rethink home intervention approaches.